Managing the Treasury yield curve in the 1940s - Kenneth D. Garbade (Federal Reserve Bank of New York, 2020)
This paper examines the efforts of the Federal Open Market Committee (FOMC) to first control, and later decontrol, the level and shape of the Treasury yield curve in the 1940s. The paper begins with a brief review of monetary policy in 1938 and a description of the period between September 1939 and December 1941, when the idea of maintaining a fixed yield curve first appeared. It then discusses the financing of U.S. participation in World War II and the experience with maintaining a fixed curve. The paper concludes with a discussion of how the FOMC regained control of monetary policy in the second half of the 1940s. The Committee's efforts offer two lessons in yield curve management: (1) the shape of the curve cannot be fixed independently of the volatility of interest rates and debt management policies, and (2) large-scale open market operations may be required in the course of refixing, from time to time, the shape of the yield curve.
Keywords: G28; H63; N22; 330; debt management; open market operations; yield curve management